The Impact of The Brand on The Decision of The Romanian Consumer to Buy Pharmaceutical Products - Bianca-Cristiana VOICU; Raluca-Giorgiana (POPA) CHIVU; Ionuț-Claudiu POPA; Ionuț TĂNASE; Elena-Florentina GREJDAN (Communications of International Proceedings, 2022)
Nowadays, in a very complex, competitive and crowded market, brands offer consumers the opportunity to generate their recognition. Thus, we can say that the role of a brand is to identify and differentiate a product or service from other similar products existing in a market. First of all, the brand has an intangible value, offered by the sum of the emotional associations that consumers have towards it and on the other hand the brand also has a concrete physical form being made up of its name, slogan and symbol. Therefore, the brand is always a promise to the consumer in terms of quality and satisfaction.
Keywords: marketing research; brand; brand capital; pharmaceuticals.